C++/CLI The Visual C++ Language for .NET - Hogenson, Gordon (Apress : Imprint: Apress, 2007)
C++/CLI: The Visual C++ Language for .NET introduces Microsoft's extensions to the C++ syntax that allow you to target the common language runtime the key to the heart of the .NET 3.0 platform. In 12 no-fluff chapters, Microsoft insider Gordon Hogenson takes you into the core of the C++/CLI language and explains both how the language elements work and how Microsoft intends them to be used. Compilable code samples illustrate the syntax as simply as possible, and more elaborate code samples show how the new syntax might typically be used. The book is a beginner's guide, but it assumes a familiarity with programming basics. And it concentrates on explaining the aspects of C++/CLI that make it the most powerful and fun language on the .NET Framework 3.0. As such, this book is ideal if you're thinking of migrating to C++/CLI from another language. By the end of this book, you'll have a thorough grounding in the core language elements together with the confidence to explore further that comes from a solid understanding of a languages syntax and grammar.